Management of Hematic Mummification in a Jersey Crossbred Heifer with Vulvar Stenosis by Episiotomy - Abdul, Reshma; Sakthivel, Manokaran; Annadurai, Thangamani; Thulasiraman, Sarath (The Indian Journal of Animal Reproduction, 2025)
A case of hematic mummification in a Jersey crossbred heifer was presented. Pregnancy was terminated using  Prostaglandin F2α treatment. Since the animal had stenosis of vulva, episiotomy was performed to widen the opening of  the birth canal and the mummified fetus was delivered successfully.
Keywords: Fetal Mummification; Vulvar Stenosis; Episiotomy; Jersey Crossbred Heifer